1984
DOI: 10.1136/bjo.68.8.544
|View full text |Cite
|
Sign up to set email alerts
|

Morphological change in the corneal endothelium due to ultraviolet radiation in welders.

Abstract: SUMMARY To clarify the relationship between morphological changes in the corneal endothelium and ultraviolet (UV) radiation, specular microscopic examinations were performed on both eyes of 118 welders and 85 controls. The results showed: a decrease in the hexagonal cells in welders (20-29 years) in comparison with the controls (20-29) (p<005); an increase in the mean cell size of the endothelium and a decrease in the hexagonal cell population with increasing age in both groups; increases in standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 4 publications
2
25
1
1
Order By: Relevance
“…It is known that an unusually high dose o f U V light causes dam age to the corneal endothelium even in nor mal individuals [10,11]. Due to the defective D N A repair replication, the endothelial cells o f X P patients may be more easily damaged and reduced in number than normal cells at the usual level o f U V exposure.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that an unusually high dose o f U V light causes dam age to the corneal endothelium even in nor mal individuals [10,11]. Due to the defective D N A repair replication, the endothelial cells o f X P patients may be more easily damaged and reduced in number than normal cells at the usual level o f U V exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cell shape analysis has been shown to be more sensitive to subtle changes in the endothelial monolayer than is cell density measurement or cell area analysis. [19][20] This study was undertaken to evalu¬ ate the morphologic changes that occur in the endothelium during a five-year period after penetrating keratoplasty. The endothelium of the central graft was serially examined and photographed with a specular microscope yearly for five years after keratoplasty in 17 patients.…”
mentioning
confidence: 99%
“…40 Cell shape analysis is known to be more sensitive to subtle changes in the endothelial monolayer than is cell density or cell area analysis. 49,50 In vivo improvement in cell junctions might have been linked to the presence of factors in the aqueous humor that were absent in vitro. In vascular physiology, it has been shown that steady shear stress stimulates the cellular responses essential for vascular endothelial cell function.…”
Section: Discussionmentioning
confidence: 98%
“…40 Endothelial cell densities and morphometric analyses were made preoperatively (using the contralateral IOVS, June 2009, Vol. 50,No. 6 Transplantation of a Reconstructed Corneal Endothelium 2687 reconstructed endothelium, not grafted, cornea) and postoperatively on the same cases (n ϭ 3; 2 reconstructed and 1 control in which only the carrier was grafted).…”
Section: Corneal Endothelial Cell Densitymentioning
confidence: 96%